PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI ADMINISTRASI PADA PERUSAHAAN PT.EKSPEDISI SULAWESI JAYA RAYA - Dandy Dhammatha Budi Rungkat; Silvia Rostianingsih; Liliana - (Jurnal Infra, 2014)
Sulawesi Jaya Raya company is a company engaged in the field of services . The company serves the freight by ship . During the Company Sulawesi Jaya Raya working order shipping process take orders manually as orders , order ships and containers , renting a place in the harbor , hire a truck and driver , to bill payment . Data communication between headquarters and branch offices still use the telephone and fax . Integrated data often lead to miscommunication or billing errors , delays in delivery order handling , and error rekapan data items that have been sent or not . To produce information quickly and accurately , an enterprise must be supported by a computerized information system , but the computerized context has a very broad scope , good handling to information systems may provide an advantage over the services provided to the customers so as to create long-term relationships better. Designing the system using the Data Flow Diagram and Entity Relationship Diagram . The program uses the MySQL Server as a database , and using the PHP programming language . The scope of the program includes creating a master database created for the city , customer , ship , ship schedules , user and price . Delivery transactions include transactions and  receipts, delivery orders include delivery delivery, table of contents , list of fit , the minutes and bills , letters and claim road , transaction admission includes a list of news events as well as the unloading and then the final bill is the automatic report generation .